Guggenheim. : New York - Venice - Bilbao - Berlin /. - Cuito, Aurora, ....-; Pons, Eugeni, ....- (Madrid : Kliczkowski, 2001)
Foreword Guggenheim International Guggenheim Bilbao Details Interiors The new Bilbao A walk through Bilbao Through the eye of the lens Appendix
Keywords: Architecten; Guggenheim; Museumgebouwen